TI_GERICHTE 14.2009.10 vom 15. Mai 2009 , Rigetto definitivo. Ecezione di compensazione. Interessi di mora - TI Tribunale d'appello (2009)
Rigetto definitivo. Ecezione di compensazione. Interessi di mora